Enhancing the soil stability using biological and plastic waste materials integrated sustainable technique - Farah Atiqah Abdul Azam; Rohayu bt Che Omar; Rasyikin bte Roslan; Intan Nor Zuliana Baharudin; Nur Hidayah Mat Muchlas (Alexandria Engineering Journal, 2024)
Maintaining and enhancing soil stability for electrical pylon installation is very vital to provide an uninterrupted energy supply. Conventionally, the stability of soil is maintained using the chemical stabilization technique, which has its limitations, is not environmentally friendly, may not provide a stable soil condition in the longer term, is and prone to disruption. Therefore, in this work, a more sustainable approach is suggested where a bio-mediated technique where microbes from biological degradations of vegetables are used to integrate with polyethylene terephthalate (PET) plastic waste as a soil stabilizer. The findings of the triaxial shear test showed that the treated soil enhanced the soil’s resistance to shearing forces by 33% due to the bridging effect and soil interlocking. The combination of 20% of fermented vegetables grout liquid and 1% of PET has improved the soil's cohesion significantly. The slope stability test also proved that the PET additions could improve the factor of safety (FOS) up to 81.47% and exceed the minimum requirement of a stable design slope as compared to the untreated slope. The results proved the influence of the bio-mediated technique with different variations of PET addition is an effective method to improve the engineering properties of the slope.